Distribution of Eosinophilic Meningitis Cases Attributable to Angiostrongylus cantonensis, Hawaii - Natasha S. Hochberg (Emerging Infectious Diseases, 2007)
During November 2004–January 2005, 5 cases of eosinophilic meningitis (EM) attributable to Angiostrongylus cantonensis infection were reported in Hawaii. To determine if this temporal clustering reflected an increased incidence, we ascertained EM and A. cantonensis cases by systematic review of statewide laboratory and medical records for January 2001–February 2005 and generalized the data to population estimates. We identified 83 EM cases; 24 (29%) were attributed to A. cantonensis infection, which was included in the discharge diagnoses for only 2 cases. Comparison of A. cantonensis infection incidence rates (per 100,000 person-years) for the baseline (January 2001–October 2004) and cluster (November 2004–February 2005) periods showed statistically significant increases for the state as a whole (0.3 vs. 2.1), the Big Island of Hawaii (1.1 vs. 7.4), and Maui County (0.4 vs. 4.3). These findings underscore the need to consider the diagnosis of A. cantonensis infection, especially in the state of Hawaii.